Analisis Laporan Keuangan untuk Memgukur Kinerja Keuangan Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia - Mujari Mujari (Journal of Management and Bussines (JOMB), 2019)
This study aims to assess the financial performance of PT Telekomunikasi Indonesia Tbk by analyzing financial statements using financial ratios. The research data was obtained from the Indonesia Stock Exchange (IDX). The results showed the performance of PT Telekomunikasi Indonesia Tbk based on liquidity ratios from 2015 to 2018 was not good, where the company's Current Ratio (CR) in 2015 to 2018 was less than 100%. The solvency ratio of PT Telekomunikasi Indonesia Tbk in 2015 to 2018 is good, where the company's Debt to Assets Ratio (DAR) in 2015 to 2018 is no more than 100%. The profitability ratio of PT Telekomunikasi Indonesia Tbk in 2015 to 2018 is good, where the results of the calculation of profitability ratios are greater than the one-year time deposit interest rate. The ratio of activities of PT Telekomunikasi Indonesia Tbk in 2015 to 2018 is not good, where the Total Assets Turn Over (TATO) is less than 1, which means the company is less productive. Keywords: Financial Statement, Financial Performance, Financial Ratios